Early Childhood Development and Social Mobility in China - Xiaogang Wu (吴晓刚); Xin Li (李欣); Jia Miao (缪佳) (ECNU Review of Education)
Purpose Infancy and early childhood are critical stages for the development of both cognitive and socioemotional skills, which are predictive of subsequent academic success, labor market outcomes, and socioeconomic achievement. Empirical research both in China and in other countries has revealed that nurturing quality is increasingly divergent among social classes, leading to intergenerational accumulation of advantage/disadvantage, declining social mobility, and exacerbating class inequality. The article aims to systematically examine existing theoretical and empirical research on early childhood development and social mobility and provide a holistic comparative and analytical framework for future research in the context of China. Design/Approach/Methods This article systematically reviews relevant theories and empirical research in the field and provides preliminary findings of early childhood education investment in China, using the data from the China Family Panel Studies (CFPS). Specifically, the article focuses on the differences in early childhood education investment and child development among families of different socioeconomic statuses and discusses the potential impact of these differences on children's future development. Findings The findings of this study reveal distinct patterns in early childhood education investment and child development across diverse socioeconomic strata in China. China's initiatives to enhance children's education and human capital have robust theoretical foundations and timely policy implications. However, despite the ongoing efforts, early childhood parenting and education programs lack systematic research, emphasizing the urgent need for intervention programs and comprehensive databases to inform evidence-based policymaking. Originality/Value The article concludes with a comprehensive analytical framework for the study of early childhood development and social mobility in China, which has implications for promoting human capital investment and facilitating social mobility.